SABDARTHARATNA OF TARANATHA SARMA: A Critical Study with English Translation - Joseph, Jojo (Asian Horizons, 2011)
The Sabdartharatna of Taranatha Tarkavacaspati is a remarkable work on the philosophy of language and this research study based on it includes two parts: The first part is a critical study of the text sabdartharatna and the second part gives its critical edition with English translation. There are four chapters in the first part: the opening chapter introduces the work and its author by giving the significance, context and content of the text, the second chapter explains the linguistic elements of the text, the third chapter gives a ‘Lingo-Scriptural interpretation’ to the concept of sabdartha and the fourth chapter makes some critical observations and conclusions. In the second part, the text is given together with its English translation, in which the passage is subdivided into small units on the basis of logical division of the topic considered, and each unit has been numbered separately for easy reference. For a better understanding of the text, the translation is immediately followed by explanatory notes.